Minerals from Macroalgae Origin: Health Benefits and Risks for Consumers - Circuncisão, Ana R.; Catarino, Marcelo D.; Cardoso, Susana M.; Silva, Artur M. S. (Marine drugs, 2018)
Seaweeds are well-known for their exceptional capacity to accumulate essential minerals and trace elements needed for human nutrition, although their levels are commonly very variable depending on their morphological features, environmental conditions, and geographic location. Despite this variability, accumulation of Mg, and especially Fe, seems to be prevalent in Chlorophyta, while Rhodophyta and Phaeophyta accumulate higher concentrations of Mn and I, respectively. Both red and brown seaweeds also tend to accumulate higher concentrations of Na, K, and Zn than green seaweeds. Their valuable mineral content grants them great potential for application in the food industry as new ingredients for the development of numerous functional food products. Indeed, many studies have already shown that seaweeds can be used as NaCl replacers in common foods while increasing their content in elements that are oftentimes deficient in European population. In turn, high concentrations of some elements, such as I, need to be carefully addressed when evaluating seaweed consumption, since excessive intake of this element was proven to have negative impacts on health. In this regard, studies point out that although very bioaccessible, I bioavailability seems to be low, contrarily to other elements, such as Na, K, and Fe. Another weakness of seaweed consumption is their capacity to accumulate several toxic metals, which can pose some health risks. Therefore, considering the current great expansion of seaweed consumption by the Western population, specific regulations on this subject should be laid down. This review presents an overview of the mineral content of prevalent edible European macroalgae, highlighting the main factors interfering in their accumulation. Furthermore, the impact of using these marine vegetables as functional ingredients or NaCl replacers in foods will be discussed. Finally, the relationship between macroalgae’s toxic metals content and the lack of European legislation to regulate them will be addressed.